2013
DOI: 10.1149/2.050304jes
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Vertically Aligned One-Dimensional (1D) La(OH)3and La2O3Nanorods by Pulse Current Deposition

Abstract: Cathodic electrodeposition of La(OH)3 from lanthanum nitrate bath was performed for the first time. The deposition experiments were conducted at the pulse current mode with a typical on-time and off-time (ton = 5 s and toff = 10 s) and an average current density of 1 mA cm−2 (Ia = 1 mA cm−2) for 50 min. The prepared deposit was then heat treated at 600°C for 3h in dry air atmosphere. The products were characterized by XRD, CHN, FT-IR and SEM techniques. The results revealed that the large scale and vertically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that the simultaneous reduction of O 2 , H 2 O, and NO 3 – results in the formation of La­(OH) 3 nanostructures. However, there are no reports detailing the formation of La­(OH) 3 films resulting from the oxygen reduction reaction (ORR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the simultaneous reduction of O 2 , H 2 O, and NO 3 – results in the formation of La­(OH) 3 nanostructures. However, there are no reports detailing the formation of La­(OH) 3 films resulting from the oxygen reduction reaction (ORR).…”
Section: Resultsmentioning
confidence: 99%
“…Lanthanide hydroxides [Ln­(OH) 3 ] are used for defluoridation, in batteries, , for photoluminescence, , as supercapacitors, as absorbents, , for photoelectrochemical water splitting, as emulsifying agents, and as a precursor to lanthanide oxides . Electroprecipitation has proven to be a powerful tool to fabricate Ln­(OH) 3 nanostructures such as (La, Nd) nanowires, (La) nanotubes, nanospindles, nanorods, nanocapsules, and (La, Gd) nanoparticles . Precipitation on the electrode surface occurs in acidic or neutral solutions when the local pH near the electrode surface becomes basic during base-generating reactions, for example, NO 3 – + H 2 O + 2e – → NO 2 – + 2OH – . , Beyenal and co-workers demonstrated the correlation between La­(OH) 3 precipitation with an increase in local pH, based on electrochemical quartz crystal microbalance (eQCM) and local pH measurements. , The formation of nanometer-thick Ln­(OH) 3 films was confirmed with scanning electron microscopy (SEM), atomic emission spectroscopy (AES), and X-ray photoelectron spectroscopy (XPS) analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it also contains peaks attributed to La(OH) 3 . [49][50][51][52] Therefore, these nanorods co-existing with the main product can be assumed to be La(OH) 3 . Similar to previous reports, [46][47][48] rectangular nanosheets with an edge size on the submicrometer scale were observed.…”
Section: Preparation Of La 2 Ti 2 O 7 As a Precursor Of Latio 2 N Viamentioning
confidence: 99%
“…H 2 bubbles can also affect the surface morphology of the deposit and also act as a dynamic template for the formation and the growth of deposit. 28 In the chemical step, Mn 2+ cations can react with the OH À ions produced on electrochemical step in two different ways, which can result in the formation of MnOOH (eqn (2)) and Mn 3 O 4 (eqn (3)) deposits, as schematically shown in Fig. 4b.…”
Section: Mechanism Of Formationmentioning
confidence: 99%